TMOD-07. EVALUATING THE POWER OF PATIENT TUMOR-DERIVED ORTHOTOPIC XENOGRAFT (PDOX) MODELS OF PEDIATRIC BRAIN TUMORS TO PREDICT DRUG RESPONSES IN HUMANS - Injac, Sarah (Neuro Oncol, 2017)
Brain tumors are the leading cause of cancer-related death in children. A major for clinical drug development is the lack of model systems that can accurately predict drug responses in human patients. In order to address this issue, our lab has established a large panel (>80) of orthotopic xenograft mouse models of brain tumors that have been shown to replicate the histopathological features, invasive growth phenotypes and gene expression profiles of the original primary tumors. In addition, treatment information and clinical outcomes are available for the patients from which these models were derived. To test whether these patient tumor-derived orthotopic xenograft tumor respond to anti-cancer therapies similarly to the corresponding human primary tumors, we designed modified treatment schedules based on original patient treatment data for > 10 models of pediatric glioblastoma and 7 models of medulloblastoma and treated them accordingly. We are able to demonstrate the feasibility of combining radiation and multi-agent cytotoxic chemotherapy our mouse models. Furthermore, our results correlate with what has been seen in large scale human clinical trials with glioblastoma models showing little benefit from standard treatments while medullblastoma models show a significant increase in survival time.